Current Advances in Lanthanide‐Doped Upconversion Nanostructures for Detection and Bioapplication. Issue 10 (27th April 2016) - Chen, Cailing; Li, Chunguang; Shi, Zhan
Abstract : Along with the development of science and technology, lanthanide‐doped upconversion nanostructures as a new type of materials have taken their place in the field of nanomaterials. Upconversion luminescence is a nonlinear optical phenomenon, which absorbs two or more photons and emits one photon. Compared with traditional luminescence materials, upconversion nanostructures have many advantages, such as weak background interference, long lifetime, low excitation energy, and strong tissue penetration. These interesting nanostructures can be applied in anticounterfeit, solar cell, detection, bioimaging, therapy, and so on. This review is focused on the current advances in lanthanide‐doped upconversion nanostructures, covering not only basic luminescence mechanism, synthesis, and modification methods but also the design and fabrication of upconversion nanostructures, like core–shell nanoparticles or nanocomposites. At last, this review emphasizes the application of upconversion nanostructure in detection and bioimaging and therapy. Learning more about the advances of upconversion nanostructures can help us better exploit their excellent performance and use them in practice. Abstract : The current advances in lanthanide‐doped upconversion nanostructures for detection and bioapplication are reviewed. The upconversion luminescence mechanism and basic synthetic and modification methods of upconversion nanostructures are introduced, alongside the design and fabrication of core–shell nanocomposites. The application of upconversion nanostructures in detection, bioimaging, and biomedical therapy is also discussed.